A 4-year Study of Lymph Node Biopsy in the Patients belonging to the Labour Class (Medical Forum Monthly, 2024)
Objective: To evaluate the rate of tuberculosis and other diseases in the patients having lymphadenopathy and find out the value of lymph node biopsy in various diagnoses.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Department of surgery, Sindh Employees Social Security Hospital Landhi, Karachi and Kulsoom Bai Valika Social Security Hospital S.I.T.E, Karachi, from April 2010 to July 2013.Materials and Methods: A retrospective study of the case sheets and biopsy reports was done. The reports of the patients of all age groups ranging from 1 to 70 years who underwent lymph node biopsy were evaluated. The patients were initially treated by local G.Ps for various complaints associated with superficial lymphadenopathy. After the failure of relief by the treatment of variable period, they were referred to our hospitals. All of our patients belonged to socio-economically low labor class.Results: Out of 55 operated patients of lymph node biopsy included in this study, 19 (34.54%) were males and 36 (65.45%) were females. The majority of the patients 42 (76.36%) were those having cervical lymphadenopathy. Others were having axillary 08 (14.54%), inguinal 02 (3.63%) and mesenteric 03 (5.45%) lymphadenopath. Twenty three (41.81%) had reactive changes, 27 (49.09%) had TB, 02 (3.63%) had malignancy and 03 (5.45%) had other lesions.Conclusion: TB infection is alarmingly high in our society which is affecting the young generation. Health care authorities should address the issue. Moreover, the common tools like FNAC should be used prior to excision biopsy as it is easy, cheap and with fewer complications. It can give accurate diagnosis in many of the cases of superficial lymphadenopathies.